2017
DOI: 10.1515/sjecr-2016-0049
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity for the Prevention of Cardiovascular Diseases

Abstract: Over the last decade, the quantity and quality of scientifi c literature examining the relationship between physical activity (PA) and cardiovascular diseases (CVD) have signifi cantly increased. Data from the literature now unequivocally show that physical inactivity is one of the major risk factors for CVD. It is believed that obesity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…Research data showed that insufficient physical activity is directly related to mortality and morbidity of NCDs (Jakovljević & Đorđević, 2017;Ding, 2018;Medina et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Research data showed that insufficient physical activity is directly related to mortality and morbidity of NCDs (Jakovljević & Đorđević, 2017;Ding, 2018;Medina et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Regular physical activity brings numerous benefits which are associated with reduced risk of cardiovascular diseases. These benefits of regular exercise were also noticed in patients with established cardiovascular disease [1][2][3][4] . Regular exercise induces changes in hemodynamic and loading conditions of the heart, which can lead to a series of positive changes in the heart's structure and function 5 .…”
Section: Introductionmentioning
confidence: 92%
“…Improved oxygen supply and myocardial contractility both in health and disease, represent exercise-related cardiac adaptations 6 . In addition, the amelioration of cardiovascular capacity due to aerobic exercise training is associated with increased left ventricular (LV) mass and volume, myocyte hypertrophy, increased LV stroke volume and lower resting and submaximal heart rate (HR) 1,[6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Certain epidemiological studies have shown that the effects of physical activity can be achieved with moderate physical activity of about 150 minutes per week, while additional health benefits are obtained with an increase in the volume or intensity of physical activity. (Jakovljević & Djordjević, 2017) Šarčević et al (2014) warn that excessive salt intake in the human diet results in a drastic increase in cardiovascular diseases: numerous studies confirm that to maintain metabolic processes, a daily intake of 1.5 grams is sufficient, while the American Heart Association recommends a daily intake of 8-15 grams. In populations that consumed less than 3 grams of salt per day in the 20th century, the absence of hypertension was recorded.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%